The Effect of doses of Natural Super Phospate Fertilizer and Potassium on the Growth and Yield of Peanut Plants (Arachis hypogaea L.) - Husainah Yusuf; Jailani; Evi Apriana; Elvitriana; Ruhul Maghfirah (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of the study was to determine the proper dosage of natural phosphate and potash fertilizers for peanut growth and yield. This research was conducted in Tanjung Village, Darul Hasanah District, Southeast Aceh Regency from October to December 2020. This study used 3x3 factorial randomized block design (RBD) with 3 repeats. The results showed that the dose of Natural Super Phosphat fertilizer had a significant effect on the weight of 100 dry seeds of peanut plants.  The highest growth and soaking of dried peanut seeds tends to be obtained at a dose of Natural Super Phospat 100 kg P205 I ha. The dose of potash fertilizer had no significant effect on plant height at the age of 15, 30 and 45 watersheds, the number of well-fused pods per clump, the number of empty pods per clump, the weight of dry pods per clump, the weight of 100 dry seeds, the weight of dry seeds per net plot and the weight of dry seeds per hectare. Better growth and yield of dry seeds in peanut plants tend to be obtained with a dose of potash fertilizer of 75 kg K20 I ha. There is an insignificant interaction between the dose treatment of Natural Super Phosphate fertilizer and the dose of potassium fertilizer.